MATRAKÇI NASUH'S İZNİK CITY MINIATURE TILE APPLICATION EXAMPLE - Araz, Mehtap; Mant Menay, Selda (Atlas Journal, 2023)
Described as the Renaissance artist of the 16th century, Matrakçı Nasuh, showed herself with her unique style that she created in the Ottoman Depictional Arts and became an example for the next muralists. In the study, Matrakçı Nasuh's art was discussed and it was revealed how he came to life and reflected in his intellectual personality and works with the emphasis on language, culture and belief diversity of her period. The aim of this study is to find the city miniatures of Matrakçı Nasuh in the 16th century. It is the application of the selected Iznik city miniature sample belonging to Matrakçı Nasuh, which is examined in its historical development within the Ottoman depiction arts, to the tile surface and its evaluation in terms of traditional arts and plastics. In this study, 16th century. It is important in terms of showing the applicability of these two traditional arts in different disciplines to the tile surface and comparing the ongoing techniques from the past to the future by examining the materials, techniques and stylistic features used in the miniature art of the Ottoman period. Scanning and descriptive analysis methods were used in the research. The architecture of today's Iznik Hagia Sophia Mosque was transferred to the tile surface by modeling the technical and compositional features of Matrakçı Nasuh in the original miniature by taking photos from the front and from a bird's eye view. The applicability of these two arts, which are in different disciplines, and the findings obtained are evaluated in the conclusion section.